2007
DOI: 10.1007/s11469-007-9054-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of Opioid Dependence in Pregnancy: A Review of the Evidence

Abstract: Conventional wisdom regarding management of opioid dependence in pregnancy calls for methadone maintenance in nearly all cases. The scientific literature and historical background upon which this recommendation is based, newer evidence indicating the safety of methadone discontinuation during pregnancy and recent studies raising concerns about the effects of methadone on the fetus and neonate are reviewed. More flexibility in the management of opioid dependence during pregnancy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Opioid detoxification has been contra-indicated in both the first trimester of pregnancy because of the risk of miscarriage and in the last trimester because of the possibility of precipitating pre-term labour, fetal distress, and even stillbirth (Department of Health (England) and the devolved administrations, 2007). However, Young (Young, 2007) revealed that the underlying evidence was tentative at best and based on two case studies that had low scientific power (n = 1) and no controls (Rementeria & Nunag, 1973;Zuspan, Gumpel, Mejia-Zelaya, Madden, & Davis, 1975). The Royal College of General Practitioners', using evidence from a comparison of two self-selected Scottish groups (Hepburn, 1997), suggest that methadone detoxification can be carried out 'at any speed and at any stage' during pregnancy (Ford et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Opioid detoxification has been contra-indicated in both the first trimester of pregnancy because of the risk of miscarriage and in the last trimester because of the possibility of precipitating pre-term labour, fetal distress, and even stillbirth (Department of Health (England) and the devolved administrations, 2007). However, Young (Young, 2007) revealed that the underlying evidence was tentative at best and based on two case studies that had low scientific power (n = 1) and no controls (Rementeria & Nunag, 1973;Zuspan, Gumpel, Mejia-Zelaya, Madden, & Davis, 1975). The Royal College of General Practitioners', using evidence from a comparison of two self-selected Scottish groups (Hepburn, 1997), suggest that methadone detoxification can be carried out 'at any speed and at any stage' during pregnancy (Ford et al, 2005).…”
Section: Discussionmentioning
confidence: 99%